Biochar and silicon for sustainable agriculture in acid soil-nutrient dynamics and maize production: a review - Abubakar, Wasil; Uddin, MK; Kasim, Susilawati; Zaibon, Syaharudin; Shamsuzzaman, S.M.; Haque, ANA; Reza, A (Agricultural Research Communication Center, 2023)
The central part of the country in the world classified Maize as their staple and essential crop, but this crop cannot cultivate appropriately in acidic soil. Thus, biochar, silicon and phosphorus observation can act as an agent to improve the growth of Maize in acidic soil. Additionally, biochar, well known for its alkaline properties, can reduce soil acidification and, at the same time, improve crop production. This low pH condition was caused by aluminium, manganese and low of phosphorus. Thus, silicon and phosphorus can improve crop productivity. Using biochar as a soil amendment raises the pH value, alone or in combination. Maize (Zea mays L.) and the acidity of the soil are much related to the application of biochar combined with silicon and phosphorus. Biochar simply can reduce exchangeable soil acidity, but when combined with silicon and phosphorus, it can have a greater influence on reducing soil Al toxicity. The importance of biochar with different rates combined with silicon and phosphorus to increase the pH of soil is still an inconsistent result by various studies. This review summarizes the properties of biochar, silicon and phosphorus and provides the scientific reference for its application to archive high yield of maize and reduce the acidification effect on soil.